Children's Legal Steps for Abuse of Property by Parents for the Sake of Polygamy: A Study of Positive Legal Analysis in Mataram Baru Village, East Lampung - Kharisma, Roza; Iwannudin, Iwannudin (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
Children are legal subjects who have inherent rights, including economic rights and property ownership rights that are protected by Indonesia's positive law. However, in practice, it is still found that the misuse of children's property by parents for personal interests, including in the context of polygamy. This study aims to analyze Indonesia's positive legal arrangements in protecting children's rights to the misuse of property by parents for the sake of polygamy and examine the legal steps that can be taken by children in dealing with these problems. This research uses a qualitative approach with a type of field research conducted in Mataram Baru Village, East Lampung. Primary data was obtained through in-depth interviews with children, legal wives, and family members, while secondary data was obtained from laws and regulations, legal literature, and other supporting documents. The results of the study show that Indonesia's positive law has provided preventive, repressive, and administrative legal protection, but its implementation at the village level has not been optimal due to low legal awareness and socio-cultural factors. The novelty of this research lies in the placement of children as active legal subjects who can demand and recover their economic rights in the context of polygamous families at the local level.